Vpliv nekaterih dejavnikov na učinkovitost pisanja učencev - Ropič, Marija (Revija za elementarno izobraževanje, 2011)
The Influence of Certain Factors on the Efficiency of Young Learners' Writing. The paper introduces current issues related to systematic literacy developmentactivities using analytic-synthetic method being newly introduced in the first and no longer in the second grade of elementary school. The study stems from the concern that a shorter period of developing pre-reading and pre-writing skills affects the efficiency of literacy development. Therefore, it measures the effect of pre-reading and pre-writing exercises on the quality of young learners' writing in the first cycle of elementary school with young learners who have been systematically developing pre-reading and pre-writing skills and young learners who have hardly been given this kind of exercises. Specifically: the study examined the impact of the exercises on the basics of writing, the exercises for developing vocal awareness, and the exercises for visual perception on the effectiveness of writing by dictation. Based on class observation, the study suggests that prior to a systematic alphabetic literacy development, young learners have a heterogeneous background (knowledge of letters, reading, reading comprehension, writing) and that young learners can effectively develop literacy (as evidenced from specific categories of mistakes) irrespective of the difference in preparation of these young learners to the systematic alphabetic literacy acquisition. It also indicates that girls are more successful in writing by dictation.
Keywords: pre-knowledge; systematic alfabetic literacy development; literacy development; writing by didaction; individual categories of mistakes; didactic materials